Education on labor preperation for pregnant women and their families/ support person - Jusmawati, Jusmawati; Hasrida, Hasrida (CV. Paperhome Indonesia, 2024)
Childbirth Preparedness and readiness to face complications, also known as the childbirth planning and complication prevention program (P4K), is defined as a programmed approach to enhance the use and effectiveness of maternal health services in preparing for childbirth. Mothers who are not prepared for childbirth are one of the factors contributing to maternal mortality rates. (AKI). Many efforts have been made to support the reduction of maternal mortality rates, one of which is preparing for childbirth starting from the pregnancy period. From the initial survey at the service location, namely Puskesmas Padongko Barru, SouthSulawesi, several issues were found, particularly concerning pregnant women, one of which is the issue of childbirth preparation, including physical, mental, and emotional readiness as well as childbirth accompaniment. The objective of this service is to identify pregnant women, ensure the existence of birth planning for pregnant women, including birth assistant plans, birth companion plans, birth location plans, potential blood donor plans, transportation plans to the birth location, and birth financing plans, including the use of postnatal family planning methods agreed upon by the pregnant women, their husbands, and families. Italso aims to ensure quick and accurate decision-making in case of complications during pregnancy, childbirth, and the postpartum period, as well as support from community leaders. The methods used include counseling, discussions, and question-and-answer sessions with 8 pregnant women and 8 companions, totaling 16 people. The research results show that before the education was conducted, around 8 pregnant women were accompanied by health cadres. In discussions with the pregnant women, several issues they faced were identified, one of which was the lack of knowledge about how to prepare for the childbirth process. However, after the education was conducted, understanding and preparation for childbirth increased by approximately 96.8%